2016
DOI: 10.1177/1934578x1601100710
|View full text |Cite
|
Sign up to set email alerts
|

Eudesmane Sesquiterpenoids from the Wood of Platycarya strobilacea

Abstract: The wood of Platycarya strobilacea Sieb. et Zucc. (Juglandaceae) was used as incense. In this study, three new sesquiterpenes (2, 4, 5) and one norsesquiterpene (3) were isolated and their structures determined as 7-hydroperoxy-11-hydroxy-2,4-cycloeudesman-8-one (2), 8-hydroxy-13-nor-2,4cycloeudesman-7-en-11-one (3), 2,4-cycloeudesma-7(11), 8-dien-(12,8)-olide (4), and 8-hydroxy-8,12-peroxy-2,4-cycloeudesm-7(11)-ene (5). In addition, the absolute configuration of a previously reported sesquiterpene was revised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A 95% EtOH extract of the stem bark of P. strobilacea was subjected to column chromatography (CC) over silica gel, Sephadex LH-20, and pre-TLC to afford compounds 1-8. The structures of the known compounds phttyearynol (6), myricatomentogenin (7), and juglanin D (8) were determined by spectral data analysis and comparison with published data (Figure 1) [8][9][10]. Compound 1 was isolated as a white solid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 95% EtOH extract of the stem bark of P. strobilacea was subjected to column chromatography (CC) over silica gel, Sephadex LH-20, and pre-TLC to afford compounds 1-8. The structures of the known compounds phttyearynol (6), myricatomentogenin (7), and juglanin D (8) were determined by spectral data analysis and comparison with published data (Figure 1) [8][9][10]. Compound 1 was isolated as a white solid.…”
Section: Resultsmentioning
confidence: 99%
“…(Juglandaceae) is a deciduous shrubby tree distributed in East Asia [ 3 ]. Previous phytochemical studies have found that this species contains large amounts of ellagitannins [ 4 ], flavonoids [ 5 ], and sesquiterpenoids [ 6 , 7 ], but apparently only one cyclic diarylheptanoid (i.e., platycarynol) [ 8 ]. Since a number of cyclic diarylheptanoids have been isolated from many species of Juglandaceae, in this paper we described the results of an extensive investigation of the stem bark of P. strobilacea in which eight cyclic diarylheptanoids, including five new ones (compounds 1 – 5 ), were isolated and identified.…”
Section: Introductionmentioning
confidence: 99%